Qualitative phenolic profile (HPLC-DAD-MS) from olive oil mill waste waters at different states of storage and evaluation of hydrolysis process as a pretreatment to recover their antioxidants - Gómez-Caravaca, A.M.; Cerretani, L.; Segura-Carretero et al., A. (Progress in Nutrition, 2011)
SummaryOlive oil mill waste water (OOMWW) represents a waste that it is generated during the extraction process of olive oil from olives and it is an important environmental problem because of the huge volume generated in the mills. Nevertheless, it is highlighted in literature the high concentration of antioxidants, especially phenolic compounds, in the OOMWW. Principally, the qualitative phenolic profiles of OOMWW differ depending on the technological process of production of olive oil and the time of storage. The aim of this work was to compare qualitatively the phenolic profile of OOMWW by HPLC-DAD-MS. Glucosilated secoiridoids as oleuropein and ligstroside, their aglycon derivatives and simple phenols were the principal compounds found in these matrixes. Furthermore, different hydrolysis reactions have been studied for the phenolic fraction in the oleuropein standard as well as in the OOMWW samples. These steps have been evaluated as pretreatment for the selection and a possible subsequent recovery of most interesting phenolic compounds as hydroxytyrosol that has been proved to possess an important antioxidant activityProfilo fenolico qualitativo (HPLC-DAD-MS) di acque reflue di vegetazione dell’industria olearia a diversi stadi di conservazione e valutazione dell’idrolisi quale pretrattamento per il recupero degli antiossidantiRiassuntoLe acque reflue di vegetazione (AV) dell’industria olearia rappresentano un rifiuto generato dal processo di estrazione dell’olio dalle olive e pertanto sono un problema ambientale per l’elevato volume generato presso gli impianti di produzione. Tuttavia, è nota dalla letteratura, l’elevata concentrazione nelle AV di composti antiossidanti a struttura fenolica. I profili fenolici qualitativi delle AV differiscono principalmente in funzione delle condizioni di produzione e delle modalità e tempi di conservazione. Questo lavoro ha l’obiettivo di confrontare qualitativamente i profili fenolici delle AV mediante analisi HPLC-DAD-MS. Nelle acque reflue di vegetazione appena prodotte sono state ritrovate principalmente secoiridoidi glicosilati (oleuropeina e ligstroside) nonché le loro forme derivate agliconiche e basse concentrazioni di fenoli semplici. Allo stesso tempo sullo standard puro di oleuropeina e sugli stessi campioni di AV sono state indagate diverse modalità di idrolisi della frazione fenolica. Tale operazione è stata valutata come pretrattamento per la selezione e l’eventuale successivo recupero dei composti fenolici di maggiore interesse come l’idrossitirosolo al quale è riconosciuta una elevata attività antiossidante.